Effects of obesity on health-related quality of life in juvenile-onset systemic lupus erythematosus. (February 2015) - Mina, R; Klein-Gitelman, M S; Nelson, S; Eberhard, B A; Higgins, G; Singer, N G; Onel, K; Tucker, L; O'Neil, K M; Punaro, M; Levy, D M; Haines, K; et al.
Objective: This study evaluated the effects of obesity on health-related quality of life (HRQOL) measures in juvenile-onset systemic lupus erythematosus (jSLE). Methods: Obesity was defined as a body mass index (BMI) ≥95th percentile according to the Sex-specific Center for Disease Control BMI-For-Age Charts and determined in a multicenter cohort of jSLE patients. In this secondary analysis, the domain and summary scores of the Pediatric Quality of Life (PedsQL) Inventory and the Child Health Questionnaire (CHQ) of obese jSLE patients were compared to those of non-obese jSLE patients as well as historical obese and non-obese healthy controls. Mixed-effects modeling was performed to evaluate the relationship between obesity and HRQOL measures. Results: Among the 202 jSLE patients, 25% ( n =  51) were obese. Obesity had a significant negative impact on HRQOL in jSLE, even after adjusting for differences in current corticosteroid use, disease activity, disease damage, gender and race between groups. Obese jSLE patients had lower physical functioning compared to non-obese jSLE patients, and to non-obese and obese healthy controls. Compared to their non-obese counterparts, obese jSLE patients also had worse school functioning, more pain, worse social functioning and emotional functioning. Parents of obese jSLE patients worry more. The CHQ scores for obese jSLE patients were also worse compared to non-obese jSLE patients in several other domains. Conclusion: Our study demonstrates the detrimental effects of obesity on patient-reported outcomes in jSLE. This supports the importance of weight management for the therapeutic plan of jSLE.